Perempuan, Jilbab, dan Solidaritas Kemanusiaan: Studi Gerakan Perempuan Berhijab Pasca Tragedi New Zealand - Wildani Hefni (Sawwa: Jurnal Studi Gender, 2019)
The movement of humanities solidarity that is widely voiced is the women's movement specifically to wear the hijab (hijab) as a form of solidarity with Muslims. women take a role that is based on the awareness of the importance of togetherness wearing headscarves as a symbol of strength to reject any rhetoric of hatred on any basis, be it identity, religion, race, and ethnicity. This paper describes the veiled women's movement as a form of humanitarian solidarity in the aftermath of the New Zealand tragedy. A descriptive qualitative study of library research was conducted using the Durkheiminism approach. This study produces findings that the hijab has a symbol of religious meaning that is closely related to solidarity and social identity. The veil becomes a symbol of social solidarity as well as resistance to abuse. The hijab movement was born as a collective act to revive the spirit of togetherness among religious followers in combating various acts of radicalism and terrorism.